Eat Your Children - O'Brien, Treasa; O'Leary, Mary Jane (Ireland : Stinging Hornet Flims, 2015)
'Eat Your Children' is an activist film that attempts to document the invisible. It tells the story of a road-trip taken by two friends attempting to emigrate from Ireland during the financial crash of 2008. The narrative follows the young women during their return to Ireland to probe the country about it's so-called acceptance of debt and austerity. The documentary uses a mixture of archival material, voxpop and observational footage through a visual-essay style to develop a rich tapestry or audiovisual material. The film immerses us into the worlds of the protagonist-come-filmmakers, two Irish women living and working in London and Barcelona, who return to Ireland to discover the modern incarnations of Irish identity, post-colonialism, nationalism, globalization and resistance.
Verzio Film Festival Submission
Keywords: Documentary films